2019
DOI: 10.15640/jpbs.v7n1a7
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Connection between Parenting Styles, Birth Order, Personality, and Sibling Relationships

Abstract: The purpose of the current study was to examine the potential effects of parenting styles and birth order on personality and sibling relationships. Two hundred forty-seven participants completed a demographics questionnaire as well as the Lifespan Sibling Relationship Scale (LSRS) to measure affect, behavior, and cognitions associated with the sibling relationship in both childhood and adulthood. They also completed the Big Five Inventory (BFI) as well as reported on which parenting style their mother and fath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(24 reference statements)
2
1
0
Order By: Relevance
“…Additionally, our study contributes to the understanding of parental involvement in sibling conflict by identifying patterns specific to our sample population that is of young adults, thereby reinforcing the idea of indirect and direct relationships between parental behavior and sibling relationship quality. This alignment between our findings and the results of (12) strengthens the validity of our conclusions regarding the role of parental factors in shaping sibling dynamics and relationship quality among young adults in India.…”
Section: Relationship Between Paternal Parenting Styles and Sibling R...supporting
confidence: 89%
See 1 more Smart Citation
“…Additionally, our study contributes to the understanding of parental involvement in sibling conflict by identifying patterns specific to our sample population that is of young adults, thereby reinforcing the idea of indirect and direct relationships between parental behavior and sibling relationship quality. This alignment between our findings and the results of (12) strengthens the validity of our conclusions regarding the role of parental factors in shaping sibling dynamics and relationship quality among young adults in India.…”
Section: Relationship Between Paternal Parenting Styles and Sibling R...supporting
confidence: 89%
“…Thus, while some weak relationships exist, the majority of the correlations do not support rejecting the null hypotheses. In accordance with (12) , who investigated the effects of parenting styles and involvement in sibling conflict on adolescent sibling relationships, the results of the current study align with their findings regarding the influence of parenting styles on sibling relationship quality. Specifically, our research similarly found that an authoritative parenting style was associated with positive sibling relationship outcomes, such as warmth and support.…”
Section: Relationship Between Paternal Parenting Styles and Sibling R...supporting
confidence: 88%
“…Warmth is there among permissive parents, but they do not place demands on their children. Last but not least, the absent parent is a neglectful one that shows their child neither affection nor expectations [13] .…”
Section: Introductionmentioning
confidence: 99%